De Novo Donor‐Specific HLA Antibody Formation in Two Patients With Crigler‐Najjar Syndrome Type I Following Human Hepatocyte Transplantation With Partial Hepatectomy Preconditioning. Issue 3 (2nd November 2015) - Jorns, C.; Nowak, G.; Nemeth, A.; Zemack, H.; Mörk, L.‐M.; Johansson, H.; Gramignoli, R.; Watanabe, M.; Karadagi, A.; Alheim, M.; Hauzenberger, D.; van Dijk, R.; et al.
Abstract : Clinical hepatocyte transplantation is hampered by low engraftment rates and gradual loss of function resulting in incomplete correction of the underlying disease. Preconditioning with partial hepatectomy improves engraftment in animal studies. Our aim was to study safety and efficacy of partial hepatectomy preconditioning in clinical hepatocyte transplantation. Two patients with Crigler‐Najjar syndrome type I underwent liver resection followed by hepatocyte transplantation. A transient increase of hepatocyte growth factor was seen, suggesting that this procedure provides a regenerative stimulus. Serum bilirubin was decreased by 50%, and presence of bilirubin glucuronides in bile confirmed graft function in both cases; however, graft function was lost due to discontinuation of immunosuppressive therapy in one patient. In the other patient, serum bilirubin gradually increased to pretransplant concentrations after ≈600 days. In both cases, loss of graft function was temporally associated with emergence of human leukocyte antigen donor‐specific antibodies (DSAs). In conclusion, partial hepatectomy in combination with hepatocyte transplantation was safe and induced a robust release of hepatocyte growth factor, but its efficacy on hepatocyte engraftment needs to be evaluated with additional studies. To our knowledge, this study provides the first description of de novo DSAs after hepatocyte transplantation associated with graft loss. Abstract : The authors report two cases of hepatocyte transplantation with partial hepatectomy preconditioning in patients with Crigler‐Najjar syndrome type I, in which after initial successful allograft function, donor hepatocytes are lost in association with emergence of donor‐specific human leukocyte antigen antibodies.